Paper sculpture a step-by-step guide - Ziegler, Kathleen; Greco, Nick (Rockport Publishers, 1994)
"Paper Sculpture: A Step-By-Step Guide" will teach you the technical skills necessary to create visually appealing paper sculptures. Through easy to follow Photographs and text, you will learn a variety of white, coloured, painted and specialty paper techniques. The pristine beauty of paper sculpture is illustrated by nine artists who describe the curling, scoring and folding techniques used to create a wide variety of provocative paper sculptures. Full colour portfolio pieces by each artist demonstrate the myriad applications of paper as an illustrative medium. This must-have guide, for the novice or seasoned professional, will awaken your creative energy and assist you in producing your own artistic paper sculptures."--Provided by publisher.